2020
DOI: 10.3901/jme.2020.16.118
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Mechanism, Influences and Countermeasures of Polygonal Wear of High-speed Train Wheels

Abstract: :Briefly introduces the current situation of techniques and applications of China's high-speed train wheels, and the several major problems influencing the operation quality, safe operation and transportation costs of high-speed trains. In these problems the most concerned one is the wheel out of roundness or called polygonal wear of wheel. The domestic and foreign researches the polygonal wear and its countermeasures are briefly reviewed. The situation and characteristics of polygonal wear of high-speed wheel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The experimental results showed that the wheel circumferential roughness was predominated by 20 th -order wheel polygonal wear, and the resulting high frequency impact at the wheel/rail interface near 580 Hz can excite the vibration modes of the gear box, thereby the reduced fatigue life for the gear box. Similarly, the brake disc mounted on the wheelset axle have been also reported to be subjected to fatigue failure due to the combined effects of high frequency vibration and thermal loading in the braking process (Jin et al, 2020). Through the field test, Peng et al pointed out that the failure of the vertical block was related to the high order wheel polygonal wear-induced high frequency impact at the wheel/rail interface (Peng, Iwnicki et al, 2019;Peng, Han et al, 2019).…”
Section: Wheel/rail High Frequency Vibration-induced Vibration Fatigu...mentioning
confidence: 99%
“…The experimental results showed that the wheel circumferential roughness was predominated by 20 th -order wheel polygonal wear, and the resulting high frequency impact at the wheel/rail interface near 580 Hz can excite the vibration modes of the gear box, thereby the reduced fatigue life for the gear box. Similarly, the brake disc mounted on the wheelset axle have been also reported to be subjected to fatigue failure due to the combined effects of high frequency vibration and thermal loading in the braking process (Jin et al, 2020). Through the field test, Peng et al pointed out that the failure of the vertical block was related to the high order wheel polygonal wear-induced high frequency impact at the wheel/rail interface (Peng, Iwnicki et al, 2019;Peng, Han et al, 2019).…”
Section: Wheel/rail High Frequency Vibration-induced Vibration Fatigu...mentioning
confidence: 99%